2020
DOI: 10.1016/s2542-5196(19)30262-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exposure to ambient fine particulate matter and out-of-hospital cardiac arrest: a nationwide case-crossover study in Japan

Abstract: Background PM 2•5 is an important but modifiable environmental risk factor, not only for pulmonary diseases and cancers, but for cardiovascular health. However, the evidence regarding the association between air pollution and acute cardiac events, such as out-of-hospital cardiac arrest (OHCA), is inconsistent, especially at concentrations lower than the WHO daily guideline (25 µg/m³). This study aimed to determine the associations between exposure to ambient air pollution and the incidence of OHCA.Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…According to a latest study of Japan, short-term exposure to PM2.5 was indicated to increase the risk of cardiac arrest out of hospital. 19 Thus, amount of clinical researches have revealed that short-term and long-term exposure to PM2.5 would increase incidence of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…According to a latest study of Japan, short-term exposure to PM2.5 was indicated to increase the risk of cardiac arrest out of hospital. 19 Thus, amount of clinical researches have revealed that short-term and long-term exposure to PM2.5 would increase incidence of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the yearly PM 2.5 average exposure limits set by the European authorities and World Health Organization (WHO) are 25 and 10 µg m -3 , respectively (EU, 2008;EEA, 2017). However, even short-term exposure to low levels of PM can lead to negative impact on health (Zhao et al, 2020). With every 10 µg m -3 increase in PM 2.5 exposure there can be a 2.8% increase in PM-related mortality (Kloog et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is no safe level of air pollution and people need information to be able to protect themselves from bushfire smoke . The article by Vardoulakis and colleagues describes how current health protection messages provide advice for only short episodes of exposure and are not suitable when exposure is sustained, as has recently been the case …”
mentioning
confidence: 99%